Endless enigma eight centuries of fantastic art - Hall, Nicholas; Ades, Dawn 1943-; Berggruen, Olivier 1963-; Marandel, J. Patrice (David Zwirner Books, 2019)
Lineages of the eerie, the strange and the fantastical: from Blake, Goya and Redon to Borremans, Yuskavage and Marshall. 'Endless Enigma: Eight Centuries of Fantastic Art' explores the ways in which artists have sought to explain their world in terms of an alternate reality, drawn from imagination, the subconscious, poetry, nature, myth and religion. 'Endless Enigma' takes as its point of departure Alfred H. Barr Jr.s legendary 1936 exhibition at the Museum of Modern Art, New York, Fantastic Art, Dada, Surrealism, which not only introduced these movements to the American public, but also placed them in a historical and cultural context by situating them among artists from earlier centuries. Presenting works from the 12th century to the present day, the book is organized into six themes: Monsters & Demons, Dreams & Temptation, Fragmented Body, Unconscious Gesture, Super Nature and Sense of Place. Works included range from medieval gargoyles to 20th-century works by Louise Bourgeois, Sigmar Polke and Pablo Picasso as well as contemporary works by Michaël Borremans and Marcel Dzama. Masterworks from the likes of Piero di Cosimo, Francisco de Goya and Titian are considered alongside those by William Blake and Odilon Redon. Time folds and temporal barriers collapse when Damiano Cappelli meets Edvard Munch, and Salvator Rosa encounters Lisa Yuskavage
Impressum: Published by David Zwirner Books on the occasion of "Endless Enigma: Eight Centuries of Fantastic Art", David Zwirner, New York, September 12-October 27, 2018
Keywords: Barr, Alfred H. -- 1902-1981; The Museum of Modern Art -- New York, NY; Geschichte 1100-2000; Geschichte 1936-; Dämon -- Motiv; Motiv; Ungeheuer; Fantastische Kunst; Versuchung -- Motiv; Kunst; Dadaismus; Traum -- Motiv; Rezeption; Surrealismus; Art / History; Fantasy in art; Surrealism; Ausstellungskatalog -- Gallery David Zwirner -- 12.09.2018-27.10.2018 -- New York, NY; Bildband